Splitting expansion and palatal approach technique for implant placement in severely resorpted maxilla (Research, Society and Development, 2021)
The treatment of patients with atrophic maxillary alveolar ridge who need oral rehabilitation is a common problem in Implant Dentistry. One of the techniques used is the alveolar ridge splitting technique to expand alveolar ridges with a horizontal bone decrease. The palatal approach technique is also recommended in cases with an insufficient thickness of the alveolar ridge for the placement of implants in the bone envelope. The aim of this work is to describe the splitting expansion and palatal approach technique for the treatment of atrophic maxillary ridges with a horizontal bone deficit and rehabilitation with implant placement. This technique combines the alveolar ridge splitting/expansion technique and the palatal approach technique. It allows alveolar ridge expansion using piezosurgery and immediate placement of implants without thread exposure in the palatal aspect. With one surgical time, this technique avoids the fracture of the buccal bone plate due to the expansion, eliminates the need for bone graft and donor-site morbidity, is simple and effective, and shows great esthetic results and implant success.